An investigation of the relationships among destination familiarity, destination image and future visit intention. Issue 3 (September 2016) - Tan, Wee-Kheng; Wu, Cheng-En
Abstract: The presence or absence of differences in the perceptions of previous visitors and non-visitors toward a destination is important to tourist theorists and practitioners. Destination familiarity, destination image, and future visit intention are suitable marketing variables for investigations into these two groups. Destination familiarity has been defined in many different ways. Adding to the complexity, related concepts, such as awareness, knowledge, experience, and expertise, have, in one way or another, been used in combination with familiarity. There is also inconsistency in whether familiarity is a unidimensional or multidimensional construct. Considering previous studies, Prentice (2004) provided an interrelated seven-dimension familiarity construct. Taking into account previous familiarity and familiarity-related studies and setting experiential familiarity as a moderator, this study aims to achieve a deeper understanding of familiarity by examining how Prentice's familiarity dimensions are interrelated, as well as to gain insights into the structural relationships among familiarity, destination image, and future visit intention via the comparison of previous visitors and non-visitors. Hong Kong was selected as the tourist destination, and the partial least squares method was applied to analyze 493 surveys collected from residents in Taiwan. The findings provide a range of academic and practical implications. In this light, certain previous findings may have to be reconsidered. The present work indicates the importance of experience as a criterion for segmenting consumers, and it demonstrates the usefulness of a critical examination of non-visitors. This study offers numerous suggestions regarding how destination marketing organizations can formulate effective strategies for both previous visitors and non-visitors. Highlights: The concept of familiarity is defined, operationalized and used in various ways. Considers relationships among different destination familiarity dimensions. Showes relationships among familiarity, destination image and visit intention. Reveals the different effects of informational and educational familiarity. Shows the showed importance of experiential familiarity dimensions as criteria to segment visitors.